(untitled) (Journal of the College of Education for Women, 2019)
In the age of information and communication revolution, education as one of lifeaspects has influenced with that revolution by integrating technology in education, whichhave become as an important learning tools of the whole educational process . Technology,when used appropriately, can help make science classroom a site of active learning andcritical thinking, furthering student inquiry and connections with different materials. It isnecessary to develop human rights education programs and materials for discretionary andextracurricular activities as it provide them with the skills and tools so that they areempowered to take action to realize their rights. Human rights education is a critical means ofinstilling the knowledge، skills ، attitudes and values that can foster a culture of humanrights، improving a shared language around the world of equality، non-discrimination،inclusion، respect، dignity and participation that is crucial to the goal of achieving a morepeaceful and just global society.